2006
DOI: 10.1002/ajpa.20423
|View full text |Cite
|
Sign up to set email alerts
|

Variability in habitat, diet, and social structure ofHapalemur griseus in Ranomafana National Park, Madagascar

Abstract: This study investigated the effects of habitat on the diet, population density, and social structure of a small-bodied folivore, Hapalemur griseus. Three groups of H. griseus were followed at two study sites (Tala and Vato) within Ranomafana National Park in southeastern Madagascar. These two sites differed in degree of habitat disturbance, forest composition, and forest structure, as determined by botanical plots (50 x 10 m) which were monitored twice monthly in the home ranges of three study groups (group T,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 88 publications
(108 reference statements)
0
65
2
Order By: Relevance
“…Propithecus and Hapalemur have relatively short faces, short jaws, partial symphyseal fusion, and dental features associated with breakdown of highly-resistant foods like leaves, stems, and seeds (Richard, 1978;Beecher, 1979;Ravosa, 1991;Grassi, 2006;Irwin, 2006;Vinyard et al, 2008). These features likely represent an adaptive suite for processing tough and/or high-yieldstrength foods that require great bite forces and/or many chews to process.…”
Section: Discussionmentioning
confidence: 99%
“…Propithecus and Hapalemur have relatively short faces, short jaws, partial symphyseal fusion, and dental features associated with breakdown of highly-resistant foods like leaves, stems, and seeds (Richard, 1978;Beecher, 1979;Ravosa, 1991;Grassi, 2006;Irwin, 2006;Vinyard et al, 2008). These features likely represent an adaptive suite for processing tough and/or high-yieldstrength foods that require great bite forces and/or many chews to process.…”
Section: Discussionmentioning
confidence: 99%
“…If consumers experience equal gains in spite of variation in ecology, one would expect to observe differences in population density and resource competition. Evidence for habitat-related variation in the social behavior of neighboring groups with overlapping home ranges comes from studies on lemurs and colobus monkeys (e.g., Curtis, 2004;Grassi, 2006;Harris and Chapman, 2007). Comparing data on social organization, activity budgets, and diet composition from a large number of savanna baboons, Kamilar (2006) found that variation of diet composition among geographically separated subspecies did not exceed variation within subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Species that show high dietary variability within or between sites, e.g., blue monkeys {Cercopithecus mitis; Lawes 2002), might be able to cope better with habitat alterations than species with a narrowly focused diet (e.g., bamboo lemurs; Grassi 2006). Documenting such variation can help identify which food species or nutritional components are most and least essential‱information that may be useful for decisions concerning conservation strategies, including reforestation.…”
Section: Introductionmentioning
confidence: 99%